Heat accumulation and all-optical switching by domain wall motion in Co/Pd superlattices. (28th April 2017) - Hoveyda, F; Hohenstein, E; Smadici, S
Abstract: All-optical switching by domain wall motion has been obtained in Co/Pd superlattices with a TiS oscillator. Heat accumulation is part of the switching process for our experimental conditions. Numerical calculations point to a connection between domain wall motion and in-plane heat diffusion.